Colour-tuneable solid-state fluorescence of crystalline powders formed from push–pull substituted 2, 5-diphenyl-stilbenes. Issue 54 (8th December 2022) - Pauk, Karel; Luňák, Stanislav; Růžička, Aleš; Marková, Aneta; Teichmanová, Kateřina; Mausová, Anna; Kratochvíl, Matouš; Smolka, Rastislav; Mikysek, Tomáš; Weiter, Martin; Imramovský, Aleš; Vala, Martin
Abstract : Polycrystalline powders of push–pull substituted stilbenes with various acceptors emit from blue to infrared. Exciton localization on a monomer (in J-like packing) or a stacked dimer (for H-aggregates) avoid exciton migration to the quenching sites. Abstract : The solid-state fluorescence (SSF) of eight DPA–DPS-EWG derivatives (DPA = diphenylamino, DPS = 2, 5-diphenyl-stilbene building block, EWG = electron withdrawing group) was studied. Varying the strength of the EWG enabled the tuning of the LUMO energy within a range broader than 1 eV, while the simultaneous changes of HOMO energy were less than 0.1 eV, according to cyclic voltammetry. The fluorescence maxima in dichloromethane laid between 483 and 752 nm and exhibited monoexponential decay and a photoluminescence quantum yield (PLQY) always higher than 35%. Six derivatives with a SSF PLQY higher than 10% in polycrystalline powder form continuously covered the range from 475 to 733 nm. Three components of SSF multiexponential decay, obtained by time-resolved fluorescence spectroscopy, were ascribed to exciton migration to nonfluorescent traps, and monomer-like and aggregate fluorescence. The character of the emitting aggregates was evaluated by quantum chemical modelling based on time-dependent density functional theory computations, carried out on the dimer arrangements obtained by X-ray diffractometry of the single crystals.